Perbandingan Norma Produksi Islam Dengan Produksi Pada Industri Bordir di Kecamatan Bangil (Studi Kasus Pada Perusahaan Faiza Bordir) - Wandha Cholifah Ramadan; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research aims to find out how far the implementation of Islamic production norms at Faiza Embroidery Industry in Bangil goes on. Author only implements two of four Islamic production norms, which are: to make working as a main pillar of production and to do production activity in a halal way. It uses qualitative approach by using case study method. Deep interviewand observation to informen, were used in collecting data and they are owner and employees of this industry. Secondary data were derived from journal, text books, and the other literatures. Analysis has been done by seeing a suitability between activity of the production process and Islamic production norms. It is started from finance and then to labor, salary system, and materials used.